2023
DOI: 10.3390/ijms24108531
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Genes Involved in ABA Biosynthesis and Perception during Development and Ripening of the Chilean Strawberry Fruit

Abstract: Hormones act as master ripening regulators. In non-climacteric fruit, ABA plays a key role in ripening. Recently, we confirmed in Fragaria chiloensis fruit that in response to ABA treatment the fruit induces ripening-associated changes such as softening and color development. In consequence of these phenotypic changes, transcriptional variations associated with cell wall disassembly and anthocyanins biosynthesis were reported. As ABA stimulates the ripening of F. chiloensis fruit, the molecular network involve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Nine-cis-epoxycarotenoid dioxygenase (NCED) is a key enzyme connecting the carotenoid degradation and ABA biosynthesis pathways [36]. ABA content has consistently been found to be correlated to the expression level of NCED [37]. It has been reported that the expression level of IbNCED3 is positively correlated with the total content of carotenoids in the SS8 sweet potato variety [38].…”
Section: The Accumulation Of Carotenoids In Fruits Of Different C Hum...mentioning
confidence: 99%
“…Nine-cis-epoxycarotenoid dioxygenase (NCED) is a key enzyme connecting the carotenoid degradation and ABA biosynthesis pathways [36]. ABA content has consistently been found to be correlated to the expression level of NCED [37]. It has been reported that the expression level of IbNCED3 is positively correlated with the total content of carotenoids in the SS8 sweet potato variety [38].…”
Section: The Accumulation Of Carotenoids In Fruits Of Different C Hum...mentioning
confidence: 99%